2003
DOI: 10.1038/sj.jhh.1001553
|View full text |Cite
|
Sign up to set email alerts
|

Factor analysis of possible risks for hypertension in a black South African population

Abstract: To date only a small number of studies have investigated the pattern of associations within a set of hypertension risks. The objective of this study was therefore to examine the interrelation of main hypertension risks in an African population by using factor analysis in order to detect underlying risk patterns. Subjects aged 16-70 years (N ¼ 963) were recruited from 37 randomly selected sites throughout the North West Province during 1996-1998. Exclusion criteria were pregnancy, lactation, casual visitors, dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 39 publications
3
25
0
Order By: Relevance
“…The prevalence of hypertension in sub-Saharan Africa ranged 0-12.5% for boys and 0-21.5% for girls ( Table 1). The highest prevalence rate recorded was 21.5% 31 for girls and 12.5% for boys, 32 whereas Steyn et al 30 recorded the highest total prevalence rate of 22.3% for both boys and girls in urban South African children. Misra et al 19 recorded the highest (20.0%) prevalence of BP for boys in the Asian region followed by Smith and Rinderknecht 14 in the United Staes (13.2%).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The prevalence of hypertension in sub-Saharan Africa ranged 0-12.5% for boys and 0-21.5% for girls ( Table 1). The highest prevalence rate recorded was 21.5% 31 for girls and 12.5% for boys, 32 whereas Steyn et al 30 recorded the highest total prevalence rate of 22.3% for both boys and girls in urban South African children. Misra et al 19 recorded the highest (20.0%) prevalence of BP for boys in the Asian region followed by Smith and Rinderknecht 14 in the United Staes (13.2%).…”
Section: Discussionmentioning
confidence: 93%
“…In general, the studies cited in this review classified the children as hypertensive based on the the guidelines for hypertension. 12,13,31,32,30,[33][34][35] Frontini et al 24 and Barger and Muldoon 25 classified children as hypertensive based on the 140/90 mm Hg recommendation of the WHO. It is clear from the cutoff point of these two studies together with the study of van der Sande et al 22 who used 160/95 mm Hg that the situation might be worse than it is reported in their respective area.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] As a result, black South Africans have a stroke mortality rate twice as high as that of Caucasians. 1 Multiple causative factors have been proposed to explain the high hypertension prevalence, including lower plasma renin levels, 4 sodium abnormalities, 5 epithelial sodium channel changes, 4 altered genes regulating the renin-angiotensin-aldosterone system, 4 increased peripheral vascular resistance 1 as well as increasing obesity prevalence.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] In South Africa it has been suggested that urbanisation 5 is associated with an increased risk of becoming overweight or obese. 6,7 Indeed, high levels of obesity have been identified among urbanised South Africans, particularly among black women. 5,7,8 The World Health Organization 9 has identified an increase in childhood obesity in developed countries and a high prevalence of childhood obesity has been reported in developing regions such as in Latin America.…”
mentioning
confidence: 99%